Curriculum Relevance to Employment in Indonesia - Bustan Bustan; Wahira Wahira (DIDAKTIKA, 2024)
Quality, relevance and competence are three aspects of higher education that are interrelated and have a direct contribution to increasing the nation's competitiveness in the field of human resources. This study uses qualitative research methods. The increasingly fierce competition for job seekers from higher education graduates in Indonesia demands the attention of higher education providers to always make adjustments to the curriculum. Increasing the relevance of this education should be the target of continuous quality improvement as part of an overall higher education quality assurance system.